Nuclear channel system (NCS) in normal endometrium and after hormonal stimulation - Novotný, Radko; Malínský, Jiří; Oborná, Ivana; Dostál, Jiří (Acta Universitatis Palackianae Olomucensis Facultatis medicae. Biomedical papers, 1999)
The ultrastructure of NCS was investigated in two groups of patients (15 in each) during the secretory phase of the normal menstrual cycle and after the hormonal stimulation performed in the IVF programme by GnRH-a, FSH and hCG. Three developmental stages of the NCS were classified. The most numerous were the NCS in the mature stage (type 2), less in the early developmental stage (type 1) and least in the regression stage (type 3). The simultaneous occurrence of all three types does not conform the statement of Spornitz. The proportions of the three types were identical in both investigated groups of patients. The number of NCS (per 100 of nuclei) was higher in the group after hormonal stimulation than in the normal cycle. The quantitative measurement of the NCS showed its larger size in the group after hormonal stimulation than in the normal cycle, but the differences in the shape were not significant. In the serial ultrathin sections we demonstrated the relation of NCS to the nucleolus and to the invaginations of the nuclear envelope, the formation of the electron lucent center and the spiral arrangement of the tubules. In the early regression stage we described the relation of the internal row of tubules to the formed myelin figures. We suppose that the higher number and larger size of NCS can be taken as a sign of the increased activity of the endometrium during the early secretory phase after the hormonal stimulation.
Keywords: Endometrium; Follicle Stimulating Hormone; hormon uvolňující gonadotropiny; Menstrual Cycle; endometrium; jaderný obal; Gonadotropin-Releasing Hormone; lidé; Female; menstruační cyklus; Nuclear Envelope; fertilizace in vitro; Fertilization in Vitro; choriogonadotropin; folikuly stimulující hormon; Chorionic Gonadotropin; ženské pohlaví; Humans